The Effect of Work Discipline and Supervision on the Performance of Informatics and Statistics Communication Service Employees West Bandung Regency - Milla Amallia Hadi; Ayi Muhiban (PT FORMOSA CENDEKIA GLOBAL, 2023)
This survey was conducted among DISKOMINFOTIK staff in the West Bandung district. The purpose of this study was to examine the extent to which job discipline and supervisory influences contributing or partially simultaneously to performance. Descriptive and associative methods are used US research methods. The survey sample includes 37 respondents. The sampling method uses a simple random sampling technique. The analysis method uses multiple regression analysis. A research tool with validity and reliability tests. The results showed that work discipline and supervisory variables and partially simultaneously influenced performance variables. This research means that employees can improve failed implemented work disciplines, re-evaluate supervisory systems to ensure they are functioning optimally, and improve employee performance both qualitatively and quantitatively is expected